Episodic Autobiographical Memory Impairment and Differences in Pronoun Use: Study of Self-Awareness in Functional Amnesia and Transient Global Amnesia - Becquet, Céline; Cogez, Julien; Dayan, Jacques; Lebain, Pierrick; Viader, Fausto; Eustache, Francis; Quinette, Peggy (Frontiers in Psychology, 2021)
The subjective experience associated to memory processing is the core of the definition of episodic autobiographical memory (EAM). However, while it is widely known that amnesia affects the content of memories, few studies focused on the consequences of an impairment of EAM on the subjective self, also called the I-self. In the present study, we explored the I-self in two puzzling disorders that affect EAM: functional amnesia, which has an impact on autobiographical memory, and transient global amnesia, which only affects episodic memory. I-self was assessed through an original measure of self-integration in autobiographical narratives, namely the use of general or personal pronouns. Results showed that patients with functional amnesia tended to use general pronouns, whereas patients with transient global amnesia preferentially used the first person. We discuss these results from a combined neuropsychological and psychopathological perspective, with a view to proposing an explanatory model of the links between self-awareness and the episodic component of autobiographical memory.